Retrieval of characteristic parameters for water vapour transmittance in the development of ground-based sun–sky radiometric measurements of columnar water vapour - M. Campanelli; T. Nakajima; P. Khatri; T. Takamura; A. Uchiyama; V. Estelles; G. L. Liberti; V. Malvestuto (Atmospheric Measurement Techniques, 2014)
Sun–sky radiometers are instruments created for aerosol study, but they can measure in the water vapour absorption band allowing the estimation of columnar water vapour in clear sky simultaneously with aerosol characteristics, with high temporal resolution. A new methodology is presented for estimating calibration parameters (i.e. characteristic parameters of the atmospheric transmittance and solar calibration constant) directly from the sun–sky radiometer measurements. The methodology is based on the hypothesis that characteristic parameters of the atmospheric transmittance are dependent on vertical profiles of pressure, temperature and moisture occurring at each site of measurement. To obtain the parameters from the proposed methodology some seasonal independent measurements of columnar water vapour taken over a large range of solar zenith angle simultaneously with the sun–sky radiometer measurements, are needed. In this work high time resolution columnar water vapour measurements by GPS were used as independent data set, but also the case when such measurements are not available was considered by developing the surface humidity method (SHM). This methodology makes it possible to retrieve the needed independent data set of columnar water vapour using the standard surface meteorological observations (temperature, pressure and relative humidity) more readily available. The time pattern of columnar water vapour from sun–sky radiometer retrieved using both the methodologies was compared with simultaneous measurements from microwave radiometer, radiosondings and GPS. Water vapour from sun–sky radiometer, obtained using GPS independent measurements, was characterized by an error varying from 1% up to 5%, whereas water vapour from SHM showed an error from 1% up to 11%, depending on the local columnar water occurring at the site during the year. These errors were estimated by comparing water vapour series from sun–sky radiometer against measurements taken by GPS at a nearby station. The accordance between retrievals from sun–sky radiometer and simultaneous measurements from the other instruments was found always within the error both in the case of SHM and of the GPS independent data set. Water vapour obtained using characteristic parameters of the atmospheric transmittance dependent on water vapour was also compared against GPS retrievals, showing a clear improvement with respect to the case when these parameters are kept fixed.